Estimation of radiation dose-reduction factor for cerium oxide nanoparticles in MRC-5 human lung fibroblastic cells and MCF-7 breast-cancer cells. (12th November 2018) - Abdi Goushbolagh, Nouraddin; Abedi Firouzjah, Razzagh; Ebrahimnejad Gorji, Kourosh; Khosravanipour, Mohammadjavad; Moradi, Saman; Banaei, Amin; Astani, Akram; Najafi, Masoud; Zare, Mohammad Hosein; Farhood, Bagher
Abstract: In the current study, radiation dose-reduction factor (DRF) of nanoceria or cerium oxide nanoparticles (CONPs) in MRC-5 Human Lung Fibroblastic Cells and MCF-7 Breast-Cancer Cells was estimated. Characterization of CONPs was determined using scanner electron microscope (SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM) and spectrophotometer. Then, six plans were designed with different radiation dose values on planning target value. The obtained MRC-5 and MCF-7 cells were treated with non-toxic concentrations of CONPs and then exposed. Finally, cell viability (%) of the cell lines was determined using MTT assay. The findings showed that CONPs have no significant radioprotective effect against 10 cGy radiation dose value. Nevertheless, 70 μM CONPs resulted in a significant radioprotection against 100, 200, 300, 400 and 500 cGy radiation dose values compared with the control group in MRC-5 cells. For all radiation dose values, mean cell viability (%) of MCF-7 had not increased significantly at the presence of nanoceria compared with control group. According to the findings, it was revealed that the use of CONPs have a significant radioprotective effect on normal lung cells, while they do not provide any protection for MCF-7 cancer cells. These properties can help to increase therapeutic ratio of radiotherapy.